Synthesis, Applications and Comparison of Some Phosphine Oxides and Their Salts with the Nitrogen Containing Compounds - Sekhri, Lakhdar; Abdelhafid Bebba, Ahmed; Hassini, Zineb (Asian Journal of Chemistry, 2016)
Some phosphine oxides 3, 5 and the corresponding salts 2, 4 have been successfully synthesized as well as nitrogen containing compounds amides 9, 10, 11 and azo-compounds 15, 16, 17. These synthesized products served as excellent inhibitors in the medium of 15% H2SO4 on API 5L 52X steel.